COMPARATIVE ANALYSIS OF FINANCIAL PERFORMACE BETWEEN BANK SYARIAH INDONESIA (BSI) AND BANK RAKYAT INDONESIA (BRI) IN THE DIGITAL BANKING ERA - Tatsbhita.R, Thatya Dhea; Pratiwi, Vina Anggun; Hasanah, Uswatun (I-Economics, 2025)
The purpose of this study is to research and differentiate the financial performance of Bank Syariah Indonesia with Bank Rakyat Indonesia during the 2019-2023 period in the digital banking environment. The evolution of banking digitalization has led to a transformation in operational efficacy and commercial tactics. The research was designed using a descriptive quantitative strategy mobilized with financial ratios such as Return Assets, Return Equity, BOPO, Non-Performing Financing, Non-Performing Loan, Capital Adequacy Ratio. In general, the results showed that BRI had better profitability performance in terms of ROA and ROE than BSI, and showed that the former bank utilized its assets and capital more efficiently. Meanwhile, the latter bank has a better level of capital stability and NPF ratio, which indicates smarter risk management practices. In addition, digital banking has helped make both banks more efficient in many ways as it has expanded access to their services. In conclusion, the study suggests that banks should work to improve their digital infrastructure and risk management to remain competitive in the new era.